2019
DOI: 10.1051/0004-6361/201935924
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the first heavily obscured QSO candidate at z > 6 in a close galaxy pair

Abstract: While theoretical arguments predict that most of the early growth of supermassive black holes (SMBHs) happened during heavily obscured phases of accretion, current methods used for selecting z >  6 quasars (QSOs) are strongly biased against obscured QSOs, thus considerably limiting our understanding of accreting SMBHs during the first gigayear of the Universe from an observational point of view. We report the Chandra discovery of the first heavily obscured QSO candidate in the early universe, hosted by a cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 46 publications
0
48
0
Order By: Relevance
“…Both quasars have [C II] bright companions (Decarli et al 2017;Willott et al 2017) reminiscent of ongoing mergers, and these are the only systems at redshifts z > 6 with companions detected in [C II] and in rest-frame UV Mazzucchelli et al 2019;Neeleman et al 2019). While here we report that PJ308−21 is X-ray luminous and its companion may host a heavily-obscured X-ray source, in an analysis of PSOJ167−13 (z = 6.5) Vito et al (2019a) report a detection of only one source, which also appears to be heavily-obscured. That these two quasars beyond z > 6 have both rest-frame UV-bright companions and heavily obscured quasar candidates may be in keeping with the prediction of Circosta et al (2019) that the host's interstellar medium is capable of producing significant column densities of n H around high-redshift quasars.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Both quasars have [C II] bright companions (Decarli et al 2017;Willott et al 2017) reminiscent of ongoing mergers, and these are the only systems at redshifts z > 6 with companions detected in [C II] and in rest-frame UV Mazzucchelli et al 2019;Neeleman et al 2019). While here we report that PJ308−21 is X-ray luminous and its companion may host a heavily-obscured X-ray source, in an analysis of PSOJ167−13 (z = 6.5) Vito et al (2019a) report a detection of only one source, which also appears to be heavily-obscured. That these two quasars beyond z > 6 have both rest-frame UV-bright companions and heavily obscured quasar candidates may be in keeping with the prediction of Circosta et al (2019) that the host's interstellar medium is capable of producing significant column densities of n H around high-redshift quasars.…”
Section: Discussionmentioning
confidence: 47%
“…Nevertheless, studies of individual quasars are still highly fruitful at characterizing mechanisms for early SMBH growth. For example, Bañados et al (2018) showed that AGN are already X-ray luminous at z = 7.5, Vito et al (2019a) identified a heavily obscured quasar candidate in a z = 6.5 quasar/galaxy pair, and Nanni et al (2018) found potential evidence of AGN variability and of jets from a z = 6.3 quasar.…”
Section: Introductionmentioning
confidence: 99%
“…The offset between the Xray centroid and the [C II] position of this galaxy is only ≈ 0.15 arcsec. A thorough investigation and discussion of this system has been presented separately (Vito et al 2019).…”
Section: Psoj167-13mentioning
confidence: 99%
“…X-ray observations are extremely valuable to search for binary SMBH systems, as they can also unveil highly dustobscured AGN, which are not necessarily radio-loud (e.g. Vito et al 2019). The occurrence of SMBH binaries is crucial to our understanding of galaxy formation, as they directly indicate that galaxies evolve through mergers (e.g.…”
Section: Tracing the Evolution Of Active Galaxies Using Large Samplesmentioning
confidence: 99%